Water use efficiency in a mild season and water cost of summer survival of perennial forage grasses in Mediterranean areas - Lelièvre F.; Satger S.; Volaire F. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Sixteen Mediterranean cultivars (cvs) of cocksfoot, tall fescue and phalaris were compared for water use, yield and water use efficiency (WUE) for three years in a field trial covered by rainout shelters in Montpellier (France). From October to May, all cvs were watered at the same water supply amounting to 70-80% of potential evapotranspiration. From June to September, no water was supplied and growth ceased during three months. For each cv and each growth cycle, yield and water balance were established. Pluri-annual production and interest of cvs in such semi-arid conditions ranged according to their perenniality (summer drought survival) and their average WUE during the autumn to spring growth period, which depends on growth potential at low temperatures. Unproductive water loss imposed by the climate during the survival period was not significantly different between cvs and years (83(18 mm). This water cost of summer survival amounted to 15-20% of annual rainfall.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)